2021
DOI: 10.1523/jneurosci.2889-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Aversive Conditioning of Spatial Position Sharpens Neural Population-Level Tuning in Visual Cortex and Selectively Alters Alpha-Band Activity

Abstract: Processing capabilities for many low-level visual features are experientially malleable, aiding sighted organisms in adapting to dynamic environments. Explicit instructions to attend a specific visual field location influence retinotopic visuocortical activity, amplifying responses to stimuli appearing at cued spatial positions. It remains undetermined both how such prioritization affects surrounding nonprioritized locations, and if a given retinotopic spatial position can attain enhanced cortical representati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
19
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 96 publications
12
19
2
Order By: Relevance
“…Synthesizing these findings, evidence of both generalization and sharpened tuning response patterns have been provided in human electroencephalography (EEG) research measuring visual sensory cortical responses ( Müller et al, 1998 ; Wieser et al, 2016 ), and alpha-band power, a signal reflecting attentional processing ( Deng et al, 2020 ) and heightened attentional engagement to a CS+ ( Panitz et al, 2019 ). Specifically, parietal alpha power ( Friedl and Keil, 2020 , 2021 ) and steady-state visual evoked potentials (i.e., ssVEPs) displayed Gaussian distributions across the generalization gradient ( McTeague et al, 2015 ), similar to neuroimaging work ( Greenberg et al, 2013 ; Lissek et al, 2014b ), and followed the generalization pattern shown in Figure 1A (Ghirlanda and Enquist, 2003 ). Parietal alpha-band activity (spectral power between 8 and 12 Hz) has been established as a robust index of stimulus saliency, linked to heightened attentional engagement with conditioned stimuli ( Yin et al, 2018 ).…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…Synthesizing these findings, evidence of both generalization and sharpened tuning response patterns have been provided in human electroencephalography (EEG) research measuring visual sensory cortical responses ( Müller et al, 1998 ; Wieser et al, 2016 ), and alpha-band power, a signal reflecting attentional processing ( Deng et al, 2020 ) and heightened attentional engagement to a CS+ ( Panitz et al, 2019 ). Specifically, parietal alpha power ( Friedl and Keil, 2020 , 2021 ) and steady-state visual evoked potentials (i.e., ssVEPs) displayed Gaussian distributions across the generalization gradient ( McTeague et al, 2015 ), similar to neuroimaging work ( Greenberg et al, 2013 ; Lissek et al, 2014b ), and followed the generalization pattern shown in Figure 1A (Ghirlanda and Enquist, 2003 ). Parietal alpha-band activity (spectral power between 8 and 12 Hz) has been established as a robust index of stimulus saliency, linked to heightened attentional engagement with conditioned stimuli ( Yin et al, 2018 ).…”
Section: Introductionsupporting
confidence: 55%
“…During generalization learning, it is expected that as threat cues acquire increased task-relevance through conditioning, alpha power would show greater power reduction for the CS+ compared to the generalization stimuli. In contrast, ssVEPs recorded from occipital sites, commonly used to assess visual cortical perception, showed difference-of-Gaussian patterns (McTeague et al, 2015;Stegmann et al, 2020;Friedl and Keil, 2021). This suggests that non-sensory regions are likely to show Gaussian-like responses along a generalization gradient, while primary sensory cortices may yield sharpened tuning, both response patterns being adaptive, respectively, for optimizing perception (sharpening) and attentional orienting (generalization).…”
Section: Generalization Learningmentioning
confidence: 90%
See 3 more Smart Citations